Performance of the triangulation-based methods Of positivity-preserving scattered data interpolation - Saaban, Azizan (Pushpa Publishing House, 2011)
We present the result and accuracy comparison of generalized positivity-preserving schemes for triangular Bézier patches of 1C and 2C scattered data interpolants that have been c on structed. We compare three methods of 1C schemes using cubic triangular Bézier patches and one 2C scheme using quintic triangular Bézier patches.Our test case consists of four sets of node/test function pairs, with node-count ranging from 26 to 100 data points. The absolute maximum and mean errors are computed using 33×33 evaluation points on a uniform rectangular grid.